2014
DOI: 10.1088/0029-5515/55/1/013007
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of plastic deformation and gas retention in tungsten

Abstract: Taking the example of tungsten, we demonstrate that high-flux plasma exposure of recrystallized and plastically deformed samples leads to principal differences in the gas trapping and associated surface modification. Surface of the exposed predeformed samples exhibits ruptured µm-sized blisters, a signature of bubbles nucleated close to the surface on the plastically induced dislocation network. Contrary to the recrystallized samples, no stage attributable to gas bubbles appeared in the desorption spectrum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Thermal drifts were below 0.05 nm s −1 . The black spectrum reveals two peaks, one around 510 K and one around 760 K, consistent with previous studies on deuterium retention in tungsten [19,58,59]. The trapping density and trapping energy are estimated by matching the TMAP7 simulation to the experimental data.…”
Section: Spherical Nanoindentationsupporting
confidence: 85%
“…Thermal drifts were below 0.05 nm s −1 . The black spectrum reveals two peaks, one around 510 K and one around 760 K, consistent with previous studies on deuterium retention in tungsten [19,58,59]. The trapping density and trapping energy are estimated by matching the TMAP7 simulation to the experimental data.…”
Section: Spherical Nanoindentationsupporting
confidence: 85%
“…This work is a continuation of our recent study addressing the role played by heavy plastic deformation on D retention and surface microstructure evolution [13][14][15]. Those works have demonstrated that plastically induced dislocation network enhances deuterium retention and amplifies the release stage around 450-600 K. Here, we provide the microstructural characterizatization of nano-and micro-scale defects that appeared as a result of plasma exposure.…”
Section: Introductionmentioning
confidence: 71%
“…Our earlier works have shown that the initial dislocation density plays a very important role in the trapping and release of hydrogen and helium in W studied under ITER-relevant plasma exposure conditions [27][28][29][30] . The initial dislocation network creates additional trapping sites and promotes strong trapping, which should be seen as a negative impact.…”
Section: Introductionmentioning
confidence: 98%